A Foresight Study of Internet of Things (IOT) on Tourism Industry in Malaysia - Nurul Nadia Farhana Borhanodin; Fazian Hashim (Research in Management of Technology and Business, 2024)
The Internet of Things (IoT) has transformed the hotel and tourism industries by integrating physical and virtual worlds through electronic devices. This evolution presents opportunities for new services, enhanced efficiency, and improved user experiences. Some organizations have already incorporated IoT into their operations, aiming to optimize client experiences. However, there are limited amount of information available about what is affecting the fast-growing of Internet of Things (IoT) in tourism industry. Therefore, this study will be conducted as a reference to know more details about factors related to Internet of Things (IoT) in tourism industry in Malaysia. The objective of conducting this study is to identify the challenges, trends, and issues and to determine the key drivers on implementing internet of things (IoT) on tourism industry in Malaysia.This study also aims to To explore the future image of the implementation of internet of things (IoT) on tourism industry in Malaysia. Researcher has decided to conduct the survey at Petaling Jaya, Selangor. The target population of respondent for this study is employees of Malaysia’s Ministry of Tourism, Arts, and Culture, Petaling Jaya (MOTAC). The study employed quantitative research approach to conduct the survey. A questionnaire was established and distributed to targeted employees. The data will be analyse by using Statistical Package for Social Science (SPSS). The results of this study are expected to provide valuable insights privacy concern and cybersecurity threats in the tourism sector.